Crisis leadership for place – an analysis of the Gauteng city-Region leadership response to the COVID-19 pandemic - Thilgavathie Naicker (Social Sciences and Humanities Open)
The COVID-19 pandemic presented a global crisis that manifested differently across scales, triggering multiple interrelated crises, including economic and social disruptions. The impact of the pandemic on city-regions worldwide has necessitated a re-evaluation of leadership practices, prompting leaders to reflect critically on how to navigate a future defined by equity, sustainability, and democracy within regional governance structures.Place-based leadership, a concept that emerged in the mid-2000s, posits that leadership should be distributed across society, with local leaders playing a pivotal role in addressing local challenges through context-specific solutions. This paper expands on the concept of place leadership by examining how leadership adapts to, manages, and copes with crises. Utilising a framework developed from existing literature and practical experience as a key respondent during the COVID-19 pandemic in Gauteng, the study adopts a mixed-methods approach. Data is drawn from twenty-seven interviews with key stakeholders in the Gauteng City-Region as well as secondary analysis of the Quality-of-Life VI 2020/2021 survey.The findings reveal that while the leadership responded swiftly to the pandemic, their crisis management was largely shaped by the national government's directives. This paper concludes with recommendations for future research into place leadership and crisis leadership, particularly within the context of city-regions.